Docking- and pharmacophore-based virtual screening for the identification of novel Mycobacterium tuberculosis protein tyrosine phosphatase B (MptpB) inhibitor with a thiobarbiturate scaffold - Zhang, Dongfeng; Lin, Yun; Chen, Xi; Zhao, Wenting; Chen, Dongni; Gao, Meng; Wang, Qinglin; Wang, Bin; Huang, Haihong; Lu, Yongjun; Lu, Yu (Bioorganic chemistry, 2019)
[Display omitted] •A novel MptpB inhibitor was identified by performing virtual screening strategy.•Compound 15 exhibited good druggability profiles.•Compound 15 exhibited potent inhibition of intracellular Mtb growth in macrophage.•Compound 15 was an excellent lead for further elaborations to develop anti-TB agents. Mycobacterium tuberculosis (Mtb) protein tyrosine phosphatase B (MptpB) is an important virulence factor for Mtb that contributes to survival of the bacteria in macrophages. The absence of a human ortholog makes MptpB an attractive target for new therapeutics to treat tuberculosis. MptpB inhibitors could be an effective treatment to overcome emerging TB drug resistance. Adopting a structure-based virtual screening strategy, we successfully identified thiobarbiturate-based drug-like MptpB inhibitor 15 with an IC50 of 22.4 μM, and as a non-competitive inhibitor with a Ki of 24.7 μM. Importantly, not only did it exhibit moderate cell membrane permeability, compound 15 also displayed potent inhibition of intracellular TB growth in the macrophage, making it an excellent lead compound for anti-TB drug discovery. To the best of our knowledge, this novel thiobarbiturate is the first class of MptpB inhibitor reported so far that leveraged docking- and pharmacophore-based virtual screening approaches. The results of preliminary structure-activity relationship demonstrated that compound 15 identified herein was not a singleton and may inspire the design of novel selective and drug-like MptpB inhibitors.